On the dynamics of segregation - Jordi Jofre-Monseny; Matz Dahlberg; Peter Fredriksson (European Regional Science Association (ERSA), 2012)
Card et al (2008a) formalize a model of ethnic residential segregation where an ethnically mixed neighborhood is dynamically stable until its minority share reaches a threshold (the tipping point). Once the neighborhood has surpassed the tipping point, it will experience massive white flight. These authors propose methods to identify tipping points and, using population counts at the US Census tract level, find that tipping is a salient feature of neighborhood dynamics. The objective of this paper is to use individual register data from Sweden to provide a more complete and informative description of neighborhood tipping behavior. We find that tipping is explained by both increased out-migration and decreased in-migration of whites, although increased out-migration seems to be more important. Tipping seems to be driven by relatively rich individuals and by individuals with kids, suggesting that tipping behavior may increase segregation of whites in a number of dimensions. School grades of white students are lower in neighborhoods that have tipped, suggesting that families with kids that do well in school leave neighborhoods that are tipping.
Keywords: 330